Gut, metabolism and nutritional Support for COVID-19: Experiences from China. Issue 1 (21st December 2020) - Jiang, Hua; Zhang, Jian-Cheng; Zeng, Jun; Wang, Lu; Wang, Yu; Lu, Charles Damien; Deng, Lei; Deng, Hongfei; Wang, Kai; Sun, Ming-Wei; Zhou, Ping; Yuan, Ting; et al.
Abstract: There is little research that focuses on the relationship between the gut, metabolism, nutritional support and COVID-19. As a group of Chinese physicians, nutritionists and scientists working on the frontline treating COVID-19 patients, we aim to integrate our experiences and the current clinical evidence to address this pressing issue in this article. Based on our clinical observations and available evidence, we recommend the following practice. Firstly, the Nutritional Risk Screening 2002 tool should be used routinely and periodically; for patients with a score ≥3, oral nutritional supplements should be given immediately. Secondly, for patients receiving the antiviral agents lopinavir/ritonavir, gastrointestinal side effects should be monitored for and timely intervention provided. Thirdly, for feeding, the enteral route should be the first choice. In patients undergoing mechanical ventilation, establishing a jejunal route as early as possible can guarantee the feeding target being achieved if gastric dilatation occurs. Fourthly, we suggest a permissive underfeeding strategy for severe/critical patients admitted to the intensive care unit during the first week of admission, with the energy target no more than 20 kcal/kg/day (for those on mechanical ventilation, this target may be lowered to 10–15 kcal/kg/day) and the protein target around 1.0–1.2 g/kg/day. If the inflammatory condition is significantly alleviated, the energy target may be gradually increased to 25–30 kcal/kg/day and the protein target to 1.2–1.5 g/kg/day. Fifthly, supplemental parenteral nutrition should be used with caution. Lastly, omega-3 fatty acids may be used as immunoregulators, intravenous administration of omega-3 fatty emulsion (10 g/day) at an early stage may help to reduce the inflammatory reaction.